On mode trapping in pulsating DA white dwarf stars - Benvenuto, Omar Gustavo (2002)
The effects are explored of time-dependent element diffusion on the mode-trapping properties of DA white dwarf models with various thicknesses of the hydrogen envelope. Our predictions are compared with the standard assumption of diffusive equilibrium in the trace-element approximation. We find that element diffusion markedly weakens the presence of mode trapping originating in the outer layers of the models, even for the case of thin hydrogen envelopes.